Morphology of Brine‐Seawater Interface and Spatial Distribution of Submarine Groundwater Discharge Windows in the Muddy Coast - Yufeng Zhang; Zengbing Sun; Bingxiao Lei; Mingbo Li; Xiujun Guo; Tianyuan Zheng; Jian Luo (Geophysical Research Letters)
Abstract The brine‐seawater interface (BSI) is a unique type of groundwater‐seawater interface (GSI) characterized by the higher density of underground brine compared to seawater. This study focuses on characterizing the bay‐scale BSI morphology and identifying submarine‐groundwater discharge windows using a comprehensive in‐situ geophysical detection on the south bank of Laizhou Bay. Our findings reveal that the BSI forms an extensive mixing zone (15–20 km) without distinct contours between waters of varying salinities. The discharge windows for underground brine are located in nearshore areas with fine sand distribution and offshore pockmark areas. Hydraulic and salinity gradients drive the underground brine discharge through these windows. The aquitard window is the primary area for shallow and deep brine exchange, likely evolved from paleochannels, ancient tidal creeks, or ancient underwater barriers. These findings provide crucial modeling support for analyzing environmental evolution mechanisms and theoretical basis for planning the underground brine mining in similar coastal regions.